Participatory Management of School Principles in Building Early Childhood Education Teachers’ Professionalism: A Case Study - Kresnawaty, Anita; Shofiyullah, Shofiyullah (Edukasi, 2026)
Early Childhood Education (PAUD) teacher professionalism plays a crucial role in improving the quality of early childhood education, while school principals, as educational leaders, determine the success of teacher development and competency enhancement. This study aims to analyze the implementation of participative management by the principal in fostering PAUD teacher professionalism at RA Al Muawanah, Tasikmalaya, using the theoretical frameworks of moral leadership (Sergiovanni), developmental supervision (Glickman), and self-efficacy (Bandura). A qualitative approach with a case study design was employed, involving one principal and four teachers as participants. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was strengthened through source and method triangulation. The findings indicate that the integration of participatory planning, dialogic supervision, professional development through training and discussions, systematic performance evaluation, and motivation and rewards simultaneously enhances teacher professionalism. Teacher professionalism is most evident when the principal acts as a moral leader emphasizing ethical values, a supervisory facilitator supporting reflection and mentoring, and a provider of successful experiences that strengthen teacher self-efficacy. A supportive school culture further reinforces the effectiveness of these strategies. These findings contribute theoretically by expanding understanding of applying moral leadership, developmental supervision, and self-efficacy theories within the context of Islamic-based PAUD. Practically, this study provides guidance for school principals and policymakers in designing adaptive, value-oriented teacher development programs that sustainably enhance teacher professionalism.